Syntheses and Solid‐State Structures of Bis(dialkylstibanyl)sulfanes and ‐telluranes1. Issue 28 (13th August 2013) - Heimann, Stefan; Schulz, Stephan; Bläser, Dieter; Wölper, Christoph
Abstract: Distibines Sb2 R4 (R = Me, Et) react with elemental chalcogens (E = S, Se, Te) with insertion into the Sb–Sb bond and formation of the corresponding bis(dialkylstibanyl)sulfanes, ‐selenanes, and ‐telluranes (R2 Sb)2 E. The structures of (Et2 Sb)2 S (1 ), (Et2 Sb)2 Te (3 ), and (Me2 Sb)2 Te (4 ) were determined by single‐crystal X‐ray diffraction. The complexes either adopt a syn – syn (1, 4 ) or syn – anti conformation (3 ) in the solid state. In addition, the compounds have different intermolecular interaction modes, which depend on the bridging chalcogen and the organic substituent bound to the Sb atoms. Abstract : Bis(dialkylstibanyl)sulfanes, ‐selenanes, and ‐telluranes (R2 Sb)2 E were synthesized by reaction of Sb2 R4 (R = Me, Et) with elemental chalcogens (E = S, Se, Te) and structurally characterized by single‐crystal X‐ray diffraction. The roles of the bridging chalcogen atom and the organic substituents on the packing of the molecules and their intermolecular interactions are discussed.